THE IMPLEMENTATION OF BELANJA DAPUR MYDIN PROGRAM: AN ANALYSIS OF UiTM ASNAF STUDENTS, JOHOR BRANCH, SEGAMAT CAMPUS - Mearaj, Mahasin Saja; Abdul Rashid, Khadijah Amira (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Belanja Dapur Mydin program is one-off initiatives organized by zakat unit of Universiti Teknologi MARA (UiTM) Johor in collaboration with Majlis Agama Islam Negeri Johor (MAINJ). The program is implemented to help the non-resident of asnaf zakat of UiTM Johor in purchasing food stuff for their daily lives. This research is conducted to study the impact of financial aid from the implementation of the program to the asnaf students. This is to ensure that they can satisfy their daily necessities to survive in university life other than focus on their academic performance. This study uses qualitative method by using semi-structured interviews. The interview involves 10 non-residents of asnaf students of UiTM Johor. The interview is analyzed by using thematic approach. The result of the study shows that the informants give positive feedback after joining the program. It can be classified into freedom of finance and choice, economic benefit and daily support, appreciation and long-term hope, value of spirit and prayer and program improvement of time constraint. In conclusion, the program gives a big and positive impact towards asnaf students in terms of purchasing food for daily needs. It is also suggested that this sort of program needs to be implemented frequently with the involvement and collaboration of various organizations like educational institutions, non-governmental organization or private sectors. It is very important to ensure the program conducted remain competitive and give a long-term impact towards the asnaf students.